1999
DOI: 10.1076/ceyr.19.3.241.5318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pranidipine, a new calcium antagonist, on circulation in the choroid, retina and optic nerve head

Abstract: Pranidipine increased blood velocity and probably blood flow in the ONH, choroid, and retina of rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In the middle panel, the frequency spectrum of the spontaneous oscillations after ET-1 shows several bands corresponding to superimposed frequencies ranging from 0.01 to 0.09 Hz. In the lower panel, Fourier analysis after amlodipine shows a minor band at 0.01 Hz, so there was a marked decrease in the frequency of the oscillations agreement with several previous experimental (isolated vessel) and clinical studies showing that dihydropyridines can cause vasodilation and increase blood flow within the ocular circulation [5,23,24], although there is some controversy regarding clinical effects [25][26][27].…”
Section: Discussionsupporting
confidence: 74%
“…In the middle panel, the frequency spectrum of the spontaneous oscillations after ET-1 shows several bands corresponding to superimposed frequencies ranging from 0.01 to 0.09 Hz. In the lower panel, Fourier analysis after amlodipine shows a minor band at 0.01 Hz, so there was a marked decrease in the frequency of the oscillations agreement with several previous experimental (isolated vessel) and clinical studies showing that dihydropyridines can cause vasodilation and increase blood flow within the ocular circulation [5,23,24], although there is some controversy regarding clinical effects [25][26][27].…”
Section: Discussionsupporting
confidence: 74%
“…1998). In addition, retinal circulation can be measured in animals if a blue‐component argon laser is substituted for the diode laser (Tamaki et al. 1994, 1996b, 1999a, 2003).…”
Section: Specific Parametersmentioning
confidence: 99%
“…Ca channel blockers have been found to increase blood flow in the ONH and choroid in animal studies 10,11 . Studies in humans with normal tension glaucoma (NTG) have shown a beneficial effect in preventing visual field loss by treatment with Ca channel blockers 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Ca channel blockers have been found to increase blood flow in the ONH and choroid in animal studies. 10,11 Studies in humans with normal tension glaucoma (NTG) have shown a beneficial effect in preventing visual field loss by treatment with Ca channel blockers. 12 Whether the useful effects of the Ca channel blocker are mediated through actions on ganglion cells or indirectly through improvement of the ocular blood flow is unclear.…”
Section: Introductionmentioning
confidence: 99%